The diverse pathology and kinetics of mass, nonmass, and focus enhancement on MR imaging of the breast - Jansen, Sanaz A.; Shimauchi, Akiko; Zak, Lindsay; Fan, Xiaobing; Karczmar, Gregory S.; Newstead, Gillian M. (Journal of magnetic resonance imaging, 2011)
Purpose: To compare the pathology and kinetic characteristics of breast lesions with focus‐, mass‐, and nonmass‐like enhancement. Materials and Methods: A total of 852 MRI detected breast lesions in 697 patients were selected for an IRB approved review. Patients underwent dynamic contrast enhanced MRI using one pre‐ and three to six postcontrast T1‐weighted images. The “type” of enhancement was classified as mass, nonmass, or focus, and kinetic curves quantified by the initial enhancement percentage (E1), time to peak enhancement (Tpeak), and signal enhancement ratio (SER). These kinetic parameters were compared between malignant and benign lesions within each morphologic type. Results: A total of 552 lesions were classified as mass (396 malignant, 156 benign), 261 as nonmass (212 malignant, 49 benign), and 39 as focus (9 malignant, 30 benign). The most common pathology of malignant/benign lesions by morphology: for mass, invasive ductal carcinoma/fibroadenoma; for nonmass, ductal carcinoma in situ (DCIS)/fibrocystic change(FCC); for focus, DCIS/FCC. Benign mass lesions exhibited significantly lower E1, longer Tpeak, and lower SER compared with malignant mass lesions (P < 0.0001). Benign nonmass lesions exhibited only a lower SER compared with malignant nonmass lesions (P < 0.01). Conclusion: By considering the diverse pathology and kinetic characteristics of different lesion morphologies, diagnostic accuracy may be improved. J. Magn. Reson. Imaging 2011;33:1382–1389. © 2011 Wiley‐Liss, Inc.